Herbst appliance with skeletal anchorage versus dental anchorage in adolescents with Class II malocclusion: study protocol for a randomised controlled trial. Issue 1 (December 2017) - Batista, Klaus; Lima, Tatiana; Palomares, Nathália; Carvalho, Felipe; Quintão, Cátia; Miguel, José; Lin, Yin-Ling; Su, Ting-Li; O'Brien, Kevin
Abstract Background The Herbst appliance is an orthodontic appliance that is used for the correction of class II malocclusion with skeletal discrepancies. Research has shown that this is effective. However, a potential harm is excessive protrusion of the lower front teeth. This is associated with gingival recession, loss of tooth support, and root resorption. This trial evaluates a method of reducing this problem. Methods/Design The study is a single-center, randomised, assessor-blinded, superiority clinical trial with parallel 1:1 allocation. Male and female young people (10–14 years old) with prominent front teeth (class II, division 1) will be treated in one orthodontic clinic. Group 1 will be treated with the conventional Herbst appliance with dental anchorage and group 2 with the Herbst appliance with indirect skeletal anchorage for 12 months. The primary objective will be to compare the proclination of the lower incisors between the Herbst appliance with dental anchorage and skeletal anchorage. Secondary objectives will be to evaluate the changes occurring between the groups in the mandible, maxilla, lower and upper molars, and in gingival recession and root resorption at the end of the treatment. Additionally, the young patient's experience using the appliances will be assessed. The primary outcome measure will be the amount of lower incisor proclination at the end of treatment. This will be assessed by cone-beam computed tomography (CBCT) superimposition. Secondary outcome measures will be the changes in the mandible, maxilla, lower and upper molars at the end of treatment assessed by tomography superimposition and the young patient's experience using the appliances assessed by self-reported questionnaires and semi-structured interviews. The randomisation method will be blocked randomisation, using software to generate a randomised list. The allocation concealment will be done in opaque envelopes numbered from 1 to 40 containing the treatment modality. The randomisation will be implemented by the secretary of the Department of Orthodontics of Rio de Janeiro State University before the beginning of the study. The patients and the orthodontists who will treat the patients cannot be blinded, as they will know the type of appliance used. The technician who will take the CBCT image and the data analyst will be blinded to patients' group allocation. Discussion If this new intervention is effective, the findings can change orthodontic practice and may also be relevant to other forms of treatment in which appliances are fixed to the bones of the jaws. However, if the bone anchoring is not effective, the trial will provide much needed information on the use of this comparatively new development. Trial registration ClinicalTrials.gov, protocol ID:NCT0241812 . Registered on 26 March 2015.